High Morning SBP Linked to Cerebrovascular Events - Nichols, Emma Hitt (MD Conference Express, 2014)
Morning systolic blood pressure (SBP) is associated with increased risk of cerebrovascular events, even if clinic SBP is low. This article presents data from the Home Blood Pressure Measurement With Olmesartan Naive Patients to Establish Standard Target Blood Pressure study [HONEST; UMIN000002567; Saito I et al. Hypertens Res 2013].